Influence of Propeller on Electromagnetic Scattering Characteristics for Unmanned Combat Aircraft Vehicle - Liu Zhanhe,Miao Nan,Wang Jing,Yang Tao,Zhang Lu (Editorial Office of Aero Weaponry, 2021)
In order to study the influence of propeller on electromagnetic scattering characteristics of unmanned combat aircraft vehicle, the electromagnetic scattering analysis model of a UAV is established, and the research methods of RCS relative value for analyzing the influence of propeller on electromagnetic scattering are proposed. By physical optics method, the RCS and relative value with different frequencies and pitch angles are calculated. The results show that the propeller causes RCS curves to expand outward, and the amplitude and width of scattering peaks increase in nose and rear direction. The effect of frequency on the RCS curves is little. The oscillation of RCS relative value in nose direction, rear direction and circumferential direction increases when the frequency increases, and the value reaches 35.449 3 dB in 30° angular domain in nose direction. When the pitch angle increases, the RCS curves converge inward, and the propeller has a greater influence on RCS relative value of angular domains in nose direction, the value reaches about 28 dB in 0° pitch angle, and the value of angular domains in rear direction oscillates with the variation of pitch angle. The electromagnetic scattering is significantly enhanced by propeller at different frequencies and pitch angles, which will be an important consideration for stealth design.